Combining ability of cowpea genotypes for green grain production - dos Santos Pessoa, Angela Maria; Campos de Magalhães Bertini, Cândida Hermínia; de Lima Castro, Érika Beatriz; de Freitas, Leslyene Maria; Maia de Sousa, Tomil Ricardo (Revista Ceres, 2024)
Cowpea is a species used for various purposes, including green grain production. New cowpea cultivars should be developed to answer the growing market demands for green gains, which can be achieved via breeding programs. In this scenario, diallel cross is a breeding method that allows researchers to select the most suitable parents for hybridization. From this perspective, this study aimed to identify cowpea parents and hybrids with good combining abilities to initiate a breeding program aimed at green grain production. The experiment was developed at the Plant Science Department of the Federal University of Ceará. Fifteen treatments (five parents and ten hybrids) were set up in a randomized block design with ten replications. The variables of green pod length, green pod mass, number of grains, grain mass per green pod, and green grain length were studied in this experiment. The data were subjected to analysis of variance, test of means, and diallel analysis. The parents and hybrids showed variations for the evaluated traits. Both additive and non-additive effects influence the behavior of inherited traits. The parent CE0002 and hybrid combinations BRS Juruá x CE1002 and CE0957 x CE0002 are recommended for selection, showing desirable aspects for green grain production.